Fecal Microbiome, Metabolites, and Stem Cell Transplant Outcomes: A Single-Center Pilot Study. (4th April 2019) - Galloway-Peña, Jessica R; Peterson, Christine B; Malik, Farida; Sahasrabhojane, Pranoti V; Shah, Dimpy P; Brumlow, Chelcy E; Carlin, Lily G; Chemaly, Roy F; Im, Jin Seon; Rondon, Gabriela; Felix, Edd; Veillon, Lucas; et al.
Abstract: Background: Accumulating evidence suggests that the intestinal microbiome may dramatically affect the outcomes of hematopoietic stem cell transplant (HSCT) recipients. Providing 16S ribosomal RNA based microbiome characterization in a clinically actionable time frame is currently problematic. Thus, determination of microbial metabolites as surrogates for microbiome composition could offer practical biomarkers. Methods: Longitudinal fecal specimens (n = 451) were collected from 44 patients before HSCT through 100 days after transplantation, as well as 1-time samples from healthy volunteers (n = 18) as controls. Microbiota composition was determined using 16S ribosomal RNA V4 sequencing. Fecal indole and butyrate levels were determined using liquid chromatography tandem mass spectrometry. Results: Among HSCT recipients, both fecal indole and butyrate levels correlated with the Shannon diversity index at baseline ( P = .02 and P = .002, respectively) and directly after transplantation ( P = .006 and P < .001, respectively). Samples with high butyrate levels were enriched for Clostridiales, whereas samples containing high indole were also enriched for Bacteroidales. A lower Shannon diversity index at the time of engraftment was associated with increased incidence of acute intestinal graft-vs-host disease (iGVHD) ( P = .02) and transplant-related deaths ( P = .03). Although fecal metabolites were not associated with acute iGVHD or overall survival, patients contracting bloodstream infections within 30 days after transplantation had significantly lower levels of fecal butyrate ( P = .03). Conclusions: Longitudinal analysis of fecal microbiome and metabolites after HSCT identified butyrate and indole as potential surrogate markers for microbial diversity and specific taxa. Further studies are needed to ascertain whether fecal metabolites can be used as biomarkers of acute iGVHD or bacteremia after HSCT. Abstract : Accumulating evidence suggests that intestinal microbiome composition may dramatically impact the outcomes of hematopoietic stem cell transplant (HSCT) patients, however real-time monitoring of the microbiome using current sequencing technologies is clinically impractical. Researchers therefore evaluated the fecal excretion patterns of intestinal microbial metabolites indole and butyrate, the bacterial species associated with these changes, and how this relates to clinical outcomes in a cohort of HSCT patients in order to understand the potential for using fecal metabolites as surrogate markers for microbiome characterization.